Sentenced to science: one black man's story of imprisonment in America - Hornblum, Allen M. (Pennsylvania State University Press, 2007)
My back is on fire -- The jungle -- Bubble-eyed Butch -- Don't serve time; let time serve you -- He's got a body like Marilyn Monroe -- They called me outer limits -- Fruit up -- He still has the cork in his ass! -- Those doctors ain't interested in you -- I tried my best -- I was in some deep shit now -- My spiritual awakening -- It was a jihad -- Feeling death blow past my face -- A righteous life -- Trying to get a little justice